Efectividad de las pausas activas en la reducción del estrés laboral en el personal de salud. - Cherrez Peláez, Gabriela Estefania; Loaiza Ordoñez, Ashley Anneth (My University, 2024)
Occupational stress in nursing staff is a response to constant exposure to physically and emotionally demanding situations, aggravated by biological, chemical, and ergonomic stresses, as well as the intense pace of work. This situation contributes to the development of illnesses and psychological disorders. According to the International Labor Organization, studies indicate high rates of depression and anxiety in healthcare professionals, such as in China (50% and 45%, respectively) and Canada (47% received psychological support). In Ecuador, a study by SEK University revealed that 30% of occupational illnesses are stress related. In this context, it is important to implement active breaks, which consist of brief exercises and stretches. These can reduce feelings of mental exhaustion, increasing worker productivity and performance by releasing endorphins that reduce fatigue. Objective: To determine the effectiveness of active breaks in reducing occupational stress among healthcare personnel working in health units in District 07D02 of the city of Machala. Materials and Methods: This is a quantitative and relational research project, focusing on analyzing the results based on the measurement of the study variables and the relationship between active breaks and workrelated stress among healthcare personnel in District 07D02, Machala. A sample of 165 professionals was used, including physicians, nurses, technicians, and administrative staff. Personnel from other districts, those who did not work in these units, or those who did not agree to participate, were excluded. Data collection was conducted through a survey that included sociodemographic variables, stress levels (physical, psychological, and social dimensions), and active breaks (physical, mental, and duration). Statistical analysis was performed using IBM SPSS Statistics, presenting the results in tables with numerical values and percentages. Results: Of the 165 healthcare professionals in District 07D02, 75.2% were women and 37.6% were nurses; 72.1% workday shifts, and 37.6% have more than 10 years of experience. Regarding stress levels, the results for the physical, psychological, and social dimensions indicate that 45.1% report work overload and 61.2% report physical discomfort. Regarding active breaks, a highly positive perception was identified: 66.4% take active breaks, and more than 83% recognize their benefits in reducing stress and improving mood, relationships, and job performance.
El estrés laboral en el personal de Enfermería es una respuesta a la exposición constante a situaciones demandantes de tipo físico y emocional, agravadas por cargas biológicas, químicas y ergonómicas, así como el ritmo intenso. Esta situación contribuye al desarrollo de enfermedades y trastornos psíquicos. Según la Organización Internacional del Trabajador, estudios indican altos índices de depresión y ansiedad en profesionales de la salud, como en China (50% y 45%, respectivamente) y Canadá (47% recibió apoyo psicológico). En Ecuador, un estudio de la Universidad SEK reveló que el 30% de las enfermedades ocupacionales están relacionadas con el estrés. En este contexto, es importante implementar las pausas activas, que constan de breves ejercicios y estiramientos, permitiendo disminuir la sensación de agotamiento mental, aumentando la productividad y desempeño del trabajador al liberar endorfinas las cuales reducen la fatiga. Objetivo: Determinar la efectividad de las pausas activas en la reducción de estrés laboral en el personal de salud que labora en las unidades de salud del Distrito 07D02 de la ciudad de Machala. Materiales y métodos: La investigación es de tipo cuantitativo y relacional, centrada en analizar los resultados en función de la medición de las variables de estudio, y la relación entre las pausas activas con el estrés laboral en el personal de salud del Distrito 07D02 de Machala. Se trabajó con una muestra de 165 profesionales, incluyendo médicos, enfermeros, técnicos y personal administrativo. Se excluyó al personal de otros distritos, quienes no laboran en dichas unidades o no aceptaron participar. La recolección de datos se realizó mediante una encuesta que abarcó variables sociodemográficas, niveles de estrés (dimensión física, psicológica y social) y pausas activas (físicas, mentales y tiempos de aplicación). El análisis estadístico se realizó con IBM SPSS Statistics, presentando los resultados en tablas con valores numéricos y porcentajes. Resultados: De 165 profesionales de salud del Distrito 07D02, el 75,2% son mujeres y el 37,6% enfermeros; el 72,1% trabaja en turno diurno y el 37,6% tiene más de 10 años de experiencia. En cuanto al nivel de estrés, los resultados de las dimensiones física, psicológica y social indican que el 45,1% reporta sobrecarga laboral y el 61,2% molestias físicas; en relación con las pausas activas, se identificó una percepción altamente positiva, el 66,4% realiza pausas activas, y más del 83% reconoce sus beneficios para reducir el estrés y mejorar ánimo, relaciones y desempeño laboral.
Keywords: PAUSAS ACTIVAS; ESTRES LABORAL; CALIDAD DE LA ATENCIÓN; SALUD LABORAL